Cultural environments with more-than-human perspectives. Prototyping through research and training - Marie Davidová; Shany Barath; Susannah Dickinson (Agathón)
The paper focuses on several systemic research-by-design case studies relating ecological, technological and social systems with a more-than-human perspective. The complexity of the real requires methods that leverage digital tools and processes proposed to enable the design of more ecological, dynamic, interrelated posthuman environments. We argue that to achieve social justice, we must also reach environmental justice and become in synergy with the planet, with Gaia. This ethos is presented in multiple case studies demonstrating the relationships between designed and existing socio and environmental systems, evaluating whether our actions on the Earth and use of non-renewable resources are sustainably innovative and what this means for more inclusive practice, the academy and our pedagogical foci and design methods.